Maintain a culture of integrity at workplace during COVID-19 outbreak - Kamaludin, Nur Najwa Atirah; Ismail, Fadillah (Academic Inspired Network, 2021)
Integrity is a powerful double-edged sword for companies today, is necessary for long term success and corporate sustainability. Cultures of integrity are committed to doing the right thing, not just as a matter of marketing or positioning, but as an uncompromising stance embodied by the words and actions in any environment and situation encountered. Having integrity in the workplace has become very important these times, especially in the current situation where all countries are facing with pandemic Covid19. Hence this paper as an initiative to the employer or organization in identifying factors that ensure the stability and practice of a culture of integrity during Covid-19 by its employees in achieving the same goals in any situation in the workplace or outside the organization.